An uncommon case of blunt traumatic rupture gallbladder: A diagnostic challenge: Blunt traumatic gall bladder rupture - Phukan, Himraj; Lynser, Donboklang; Lyngwa, Gareth Yobel; Daniala, Chhunthang; Khongwar, Donkupar (The ASEAN Journal of Radiology, 2025)
Gall bladder injury secondary to blunt abdominal injuries are extremely rare and is reported in less than 2% of such cases. Clinical diagnosis is usually difficult due to absence of specific clinical symptoms. We present a case of 31-year-old man with a history of drunk driving leading to road traffic accident coming to our emergency department with mild pain in the periumbilical region. A proper diagnosis was made by ultrasound and computed tomography (CT). CT also revealed injury to the adjacent hepatic segment. The patient was successfully treated with laparotomy and cholecystectomy. Here we discuss the conditions which may predispose to a gall bladder injury and the need for early radiological diagnosis before the signs of biliary peritonitis sets in. Timely intervention carries a good prognosis